HUMAN RESOURCES MANAGEMENT THROUGH COMPETENCE AND COMPETENCIES FOR SECURITY AND DEFENCE - Dimitrova Sevdalina; Stoykov Stoyko (2020)
In response to the missions, objectives and tasks of the Armed Forces and the Bulgarian Army, the formation of the necessary operational capabilities is directly related to the needs of the defence system of highly educated officers, sergeants, soldiers, civilian employees, with managerial skills and leadership skills. The acquisition of these is the result of the functioning of the military education system (MES), whose mission is to train military and civilian persons to acquire education, qualifications, competences and formation of values and attitudes, physical and psychological qualities corresponding to the needs of Armed Forces to build the necessary operational capabilities. Its achievement is at the basis of the formation of the military profession, as with the Decree of the Council of Ministers № 205 of 30.08.2012 for adopting the ordinance on the state requirements for acquiring higher education in the specialties from military professional field, was recognized as a regulated profession. The purpose of this scientific research is to provide a scientific answer to the questions about the content and scope of regulated professions on the one hand, and on the other hand to clear the question is knowledge a resource, and finally to clear the question is competence management possible.